Moving Beyond Dyadic Ties: A Network Theory of Stakeholder Influences - Rowley, Timothy J. (Academy of Management Review, 1997)
Stakeholder theory development has increased in recent years, in part because of its emphasis on explaining and predicting how an organization functions with respect to the relationships and influences existing in its environment. Thus far. most researchers have concentrated on dyadic relationships between individual stakeholders and a focal organization. Using social network analysis, I construct in this article a theory of stakeholder influences, which accommodates multiple, interdependent stakeholder demands and predicts how organizations respond to the simultaneous influence of multiple stakeholders.